(3eNJUQ hLhg GdbQGAGJ hGdGYJdGd Ydi GdQhGjGJs - (3CMeO Hf YeGQ Hf CHj GdYHGS GdegOhj, CHh GdYHGS,J (B440 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg HLejY eMGeOg hTcQg Ydi Lejd YhGFOg hLRjd ahGFOg s
(3BNQgG (B:s
(3hGdQaY Ydi Gf GeQCJg QaY HGdEHJOGA hLeGdI NHQI hEScGf GdgGA aj dgH haJMgG GfJgi HMeO Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs